EFEK KOMBINASI BEBAN AKSIAL DAN LENTUR SERTA VARIASI BENTUK DAN UKURAN LUBANG TERHADAP KONSENTRASI TEGANGAN PADA BALOK BAJA BERLUBANG - M. Sukrawa; A. A. N. A. Angga Pradhana; G. Pringgana; K. Sudarsana; I G. A. Susila; I A. M. Budiwati (Master of Civil Engineering Program Study, Faculty of Engineering, Udayana University, 2019)
EFFECT OF COMBINED AXIAL AND BENDING LOADS AND VARYING SHAPES AND SIZES OF OPENING ON STRESS CONCENTRATION IN STEEL BEAM WITH WEB OPENINGABSTRACTResearch related to stress concentrations in perforated steel beams is usually carried out on simple beams without the influence of axial loads. In this study, modeling of 2-story steel frame structures was carried out to evaluate the effect of the combination of axial and flexural loads on the stress concentration around the opening in the steel beam. The observed opening includes square and circular opening, with and without reinforcement around the opening, with opening dimensions of 0.3 H, 0.5 H, and 0.7 H. H is the height of the beam. The types of reinforcement are All Around (AA), Long Horizontal (LH), and Doubler Plate (DP). The analysis results showed that 17% increase in beam axial force due to earthquake load, resulting in stress increase of 9% in square opening. The maximum stress around circular opening is smaller than that on the square one. The maximum stresses in the circular openings are 0.35 fy, 0.43 fy, and 0.69 fy for opening dimensions of 0.3 H, 0.5 H and 0.7 H, respectively. In the square opening, the maximum stress in 0.3 H opening is 0.57 fy, while for opening dimension of 0.5 H and 0.7 H the stresses exceeds the yield stress of the steel. Addition of AA and LH reinforcement in 0.5 H square opening, results in stresses lower than fy, whereas for the 0.7 H opening the reinforcement around the hole is ineffective.